Vom officium zum beneficium: Lokale Verwaltungsstrukturen im Johanniter-Priorat Alamania während des 13. und frühen 14. Jahrhunderts - Borchardt, Karl (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2021)
From officium to beneficium: Local government structures in the Hospitaller Priory of Alamania during the 13th and early 14th century The paper is about the appointment of commanders for Hospitaller houses in southern Germany during the second half of the thirteenth and the first half of the fourteenth century (until c. 1330). No written documents about such appointments are extant from the time and region. The names of the commanders are only known from local charters. Some commanders were changed almost annually. Others stayed on more or less for life. The Hospitaller rule, statutes and consuetudines concerning such appointments are not clear. In the fourteenth century commanders were entrusted their houses either for ten years or for life. Earlier on shorter periods are probable, five years or even only one year, until the next regional chapter. Further research should be devoted to the question whether military-religious orders started with an office whose officers was ad nutum amovibilis, and then changed to procedures known from ecclesiastical benefices held by non-religious, secular clergy for life and from fiefs held by secular knights that were also held for life.